Sources identification and contamination assessment of heavy metals in soil of Middle Nile Delta, Egypt. Issue 1 (1st January 2020) - Abu Khatita, Atef M.; Koch, Roman; Bamousa, Abdullah O.
Abstract : Sedimentological and geochemical studies are integrated to determine the potential of heavy metals in the Middle Nile Delta soil. Four sources of trace elements were identified; a geogenic source includes Fe, Co, Cr, Ni and V, along with Ca that partly enhanced by anthropogenic input, and three dissimilar anthropogenic sources grouped the elements as follow; As, Pb, Zn Cu, Ba and P which derived mainly from industrial activities; Ba, Pb, Zn and Cu group is likely dispersed by traffic emissions, and P, As and Cu elements group which influenced by agrochemical application and drain water irrigation. The concentrations of studied elements increasing with decreasing the particle size. Moreover, two groups of mineral assemblages of soil are recognized; the first group deposited with one particle fraction and inherited from parent materials, The second one includes non-silicate minerals clasts, deposited with more than one fraction and most likely of anthropogenic source.